Integrating web 2.0 technology in ESL classroom: A review on the benefits and barriers - Mohd Shakir Azfar Abdul Halim; Harwati Hashim (RedWhite Press, 2019)
In this immensely growing information and communication technology (ICT) era, technology has been a subject matter that is not “alien” any more in all fields, including the education field. Nowadays, integrating technology in teaching and learning process is seen vital and essential in its way to offer a more meaningful learning to the learners, and to produce high-quality human capital equipped with the 21st century skills. In English as a Second Language (ESL) teaching and learning particularly, there are many ways educators have used to ensure that ESL learners could benefit from incorporating technology in ESL classroom including through the use of Web 2.0 technology. This paper aims to review the benefits and barriers of integrating Web 2.0 technology in ESL classroom. This paper uses a number of journal articles and conference proceedings in aiding to find the related data. Thus, it is concluded that although integrating Web 2.0 technology in ESL classroom does come with its apparent barriers, the benefits of it towards ESL teaching and learning process and ESL learners are also evident and will be further discussed in the findings.